Diabetic ketoacidosis presented with COVID-19 infection: A rare case report - Deniz Çekiç; Selçuk Yaylacı; Sümeyye Çekiç; Kubilay İşsever; Hamad Dheir; Havva Kocayiğit; Mehmet Halil Öztürk; Oğuz Karabay (National Scientific Medical Center, 2021)
SARS-Corona Virus-2 (SARS-CoV-2/COVID-19)  Is a corona virus that first appeared in China in December 2019, causing severe acute respiratory failure. The severe infecitous disease caused by SARS-Corona Virus-2 is anounced as a pandemic at March 2020 by WHO. It has infected 4.5 million people and caused the death of 300 thousand people until today (17.05.2020). Although there may be atypical presentations, common complaints are mostly fever, cough, shortness of breath. İncreased acute phase reactants commonly spotted as laboratory findings. A peripheral infiltrations in the bilateral lungs and ground glass opasitices are characteristic findings in CT as a radiological findings. But some rare presentatiton also has been reported.  İn this case, we aimed to present Covid-19 infeciton presenting with diabetic ketoacidosis in hospital application.